Host Factors Modulate Virus-Induced IFN Production via Pattern Recognition Receptors - Wang J; Dong Y; Zheng X; Ma H; Huang M; Fu D; Liu J; Yin Q (Journal of Inflammation Research, 2024)
Jingjing Wang,1 Yirui Dong,1 Xuewei Zheng,1 Haodi Ma,1 Mengjiao Huang,1 Dongliao Fu,1 Jiangbo Liu,2 Qinan Yin1,3 1School of Medical Technology and Engineering, Henan University of Science and Technology, Luoyang, People’s Republic of China; 2Department of General Surgery, First Affiliated Hospital, College of Clinical Medicine, Henan University of Science and Technology, Luoyang, People’s Republic of China; 3Henan Engineering Research Center of Digital Pathology and Artificial Intelligence Diagnosis, The First Affiliated Hospital of Henan University of Science and Technology, Luoyang, People’s Republic of ChinaCorrespondence: Qinan Yin, School of Medical Technology and Engineering, Henan University of Science and Technology, No. 263 Kaiyuan Avenue, Luoyang, People’s Republic of China, 471003, Email qinanyin@haust.edu.cn Jiangbo Liu, First Affiliated Hospital, College of Clinical Medicine, Henan University of Science and Technology, Guanlin Avenue, Luoyang, 471031, People’s Republic of China, Email jiangboliuxing@163.comAbstract: Innate immunity is the first line of defense in the human body, and it plays an important role in defending against viral infection. Viruses are identified by different pattern-recognition receptors (PRRs) that activate the mitochondrial antiviral signaling protein (MAVS) or transmembrane protein 173 (STING), which trigger multiple signaling cascades that cause nuclear factor-κB (NF-κB) and interferon regulatory factor 3 (IRF3) to produce inflammatory factors and interferons (IFNs). PRRs play a pivotal role as the first step in pathogen induction of interferon production. Interferon elicits antiviral activity by inducing the transcription of hundreds of IFN-stimulated genes (ISGs) via the janus kinase (JAK) – signal transducer and activator of transcription (STAT) pathway. An increasing number of studies have shown that environmental, pathogen and host factors regulate the IFN signaling pathway. Here, we summarize the mechanisms of host factor modulation in IFN production via pattern recognition receptors. These regulatory mechanisms maintain interferon levels in a normal state and clear viruses without inducing autoimmune disease.Keywords: pattern recognition receptors, interferon-signaling pathway, host factors